Penerapan Model Pembelajaran Project Based Learning (Pjbl) dalam Implementasi Kurikulum Merdeka di Pendidikan Islam Anak Usia Dini - Sakila, Siti Risda; Hibana, Hibana; Tumbularani, Tumbularani (LP. Ma'arif Janggan Magetan, 2023)
This literature review aims to explore and analyze the application of the Project Based Learning (PjBL) Learning Model in the Implementation of the Independent Curriculum in Early Childhood Islamic Education. Through a literature review approach, this research aims to identify the benefits of PjBL in forming creativity, clean and healthy lifestyles, social skills, and critical thinking abilities in young children. In relation to the Independent Curriculum, this study also evaluates the extent to which PjBL is in accordance with curriculum principles which emphasize character, creativity and independence. The research focus is also focused on the impact of PjBL on early childhood Islamic education, by assessing its influence on the development of Islamic character, understanding religious values, and children's involvement in the learning process. The results of this literature review are expected to provide strategic insight for the implementation of PjBL in Independent Curriculum in Early Childhood Islamic Education. As a contribution to educational literature, this study is expected to provide a theoretical and practical basis for the development of relevant and effective learning methods in the context of early childhood Islamic education.